Determining the levels of family burden and psychological symptoms in mothers with children with cerebral palsy in Turkey - Asan, Gulsum; Soylar, Pinar (Univ South Bohemia Ceske Budejovice, Fac Health Social Sciences, 2024)
Aim: The study aims to determine the level of family burden and psychological symptoms in mothers who have children with Cerebral Methods: The descriptive study was completed with 200 mothers of children with CP. Results: Depression was found in mothers (1.11 +/- 0.79) and the Family Burden Assessment Scale (FBAS) mean score was also high (143.71 +/- 22.68). A statistically significant difference was found between mothers who received support to care for their children and their level of depression (p = 0.003). A positive and significant relationship was also found between emotional burden and psychiatric symptoms, such as anxiety, depression, negative self-perception, somatization, and hostility (r = 0.458, p = 0.001; r = 0.552, p = 0.001; r = 0.494, p = 0.001; r = 0.376, p = 0.001; r = 0.404, p = 0.001), respectively. A weak and positive relationship was determined between time requirement and psychiatric symptoms, such as anxiety, depression, and negative self-perception (r = 0.166, p = 0.019; r = 0.259, p = 0.001; r = 0.223, p = 0.001, respectively). Conclusion: The main factor affecting depression in caregivers was lack of support. As the mothers' emotional burden increases, their psychiatric symptom scores also increase. In our study, mothers' anxiety, depression, and negative self-perception scores increase as their time requirements increase. Mothers should be supported with certain interventions, such as education and instruction, to meet the necessities while caring for their children. Policymakers should support mothers with low-income levels to ensure that the required services reach their recipients. Psychological support and counseling services can be provided to the children and mothers following the diagnosis of CP.
Keywords: Caregiver; Cerebral palsy; Family burden; Mother; Psychological symptoms